The true limit distributions of the Anderson-Hsiao IV estimators in panel autoregression - PHILLIPS, Peter C. B. (Institutional Knowledge at Singapore Management University, 2015)
This note derives the correct limit distributions of the Anderson-Hsiao (1981) levels and differences instrumental variable estimators, provides comparisons showing that the levels IV estimator has uniformly smaller variance asymptotically as the cross section (n) and time series (T) sample sizes tend to infinity, and compares these results with those of the first difference least squares (FDLS) estimator. (C) 2014 Elsevier B.V. All rights reserved.